2020
DOI: 10.1111/jwas.12693
|View full text |Cite
|
Sign up to set email alerts
|

An orally delivered, live‐attenuated Edwardsiella ictaluri vaccine efficiently protects channel catfish fingerlings against multiple Edwardsiella ictaluri field isolates

Abstract: The commercial channel catfish (Ictalurus punctatus) industry is adversely impacted by enteric septicemia of catfish (ESC), caused by the Gram-negative enteric rod Edwardsiella ictaluri. In efforts to develop more effective management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
14
2
Order By: Relevance
“…This phenomenon has been described in similar studies investigating cross‐protective immunity in fish vaccines (Poobalane et al., 2010; Wang et al., 2013). In Experiment 1, post‐vaccination, prechallenge losses were inconsistent with previous studies (Aarattuthodiyil et al., 2020; Chatakondi et al., 2018; Greenway et al., 2017; Griffin, Greenway, et al., 2020; Peterson et al., 2016; Wise et al., 2015). This response could be attributed to the extremely high vaccine dose (>1 × 10 7 CFU/ml) and increased exposure time used to ensure an adequate immune response in hybrids, which are typically less susceptible to E .…”
Section: Discussioncontrasting
confidence: 69%
“…This phenomenon has been described in similar studies investigating cross‐protective immunity in fish vaccines (Poobalane et al., 2010; Wang et al., 2013). In Experiment 1, post‐vaccination, prechallenge losses were inconsistent with previous studies (Aarattuthodiyil et al., 2020; Chatakondi et al., 2018; Greenway et al., 2017; Griffin, Greenway, et al., 2020; Peterson et al., 2016; Wise et al., 2015). This response could be attributed to the extremely high vaccine dose (>1 × 10 7 CFU/ml) and increased exposure time used to ensure an adequate immune response in hybrids, which are typically less susceptible to E .…”
Section: Discussioncontrasting
confidence: 69%
“…Contrary to this line of thought, Klesius and Shoemaker () reported that channel catfish immunized by sublethal exposure to a virulent E. ictaluri isolate were not protected against all challenge isolates in a heterologous cross‐protection study. Comparably, the vaccine isolate used here was shown to protect fish against 23 temporally discrete isolates from U.S. catfish operations archived from 1993 to 2016 (Aarattuthodiyil et al, ). Moreover, using similarly produced vaccine serials, genetic variation (family effects) in host fish was not shown to influence vaccine efficacy (Peterson et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…For example, there is evidence that a live-attenuated E. ictaluri vaccine (Wise et al, 2015) can infer protection against E. piscicida in channel and hybrid catfish, although this has only been demonstrated against E. piscicida isolate S11-285, a member of the common MLSA clade 1 (Griffin et al, 2020). Although the E. ictaluri vaccine is effective against multiple E. ictaluri isolates from catfish farms in Mississippi and Alabama, molecular analysis revealed these geographically and temporally discrete isolates collected from 1993 to 2006 were largely clonal (Aarattuthodiyil et al, 2020). Given the genetic plasticity of E. piscicida in catfish aquaculture, it is prudent to evaluate protection against other E. piscicida phylogroups in future studies of E. piscicida variants from channel and hybrid catfish aquaculture.…”
Section: Discussionmentioning
confidence: 99%